Adsorption–Desorption Cycles for the Separation of Vapour-Phase Ethanol/Water Mixtures - Krzysztof Kupiec; Jan Rakoczy; Lukasz Zieliński; Andreas Georgiou (Adsorption Science & Technology)
A theoretical analysis and the results of the experimental verification of the adsorption–desorption process for ethanol dehydration are presented. This adsorption–desorption process is applied in industrial installations for the production of dehydrated ethanol as a fuel additive. In the present work, the experiments were performed using a small-scale experimental setup. The sequence of operations consisted of adsorption, vacuum desorption and purge. The adsorption column, filled with zeolite 3A pellets, was fed with a vapour-phase ethanol/water mixture containing 25 mol% water. The water vapour content at the column outlet was determined using gas chromatography. During the vacuum desorption step, the upper outlet of the column was connected to a vacuum pump. During the purge step, the lower outlet of the column was connected to a vessel containing pure ethanol while the upper outlet was connected to the vacuum pump. The process simulation results using the developed model have been compared with the experimental results in order to verify accuracy of the model. The agreement between the experimental and theoretical results demonstrated that the mathematical model adequately described the process.